2022
DOI: 10.48550/arxiv.2201.03085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disk Tearing Leads to Low and High Frequency Quasi Periodic Oscillations in a GRMHD Simulation of a Thin Accretion Disk

G. Musoke,
M. Liska,
O. Porth
et al.

Abstract: Black hole X-ray binaries (BHXRBs) display a wide range of variability phenomena, from long duration spectral state changes to short-term broadband variability and quasi-periodic oscillations (QPOs). A particularly puzzling aspect is the production of QPOs, which -if properly understood -could be used as a powerful diagnostic tool of black hole accretion and evolution. In this work we analyse a high resolution three-dimensional general relativistic magnetohydrodynamic simulation of a geometrically thin accreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
(142 reference statements)
2
7
0
Order By: Relevance
“…The results show that the Comptonization flux decreases when the disk tears, probably because the outer disc cannot maintain a sufficient gas supply (Liska et al 2021). Conversely, disk flux less than 2 keV increases slightly, which is also seen in recent simulations of Musoke et al (2022), although their main research is not type-B QPOs. They suggested that the absence of a warp in the aligned portion of the disk reduces the inflow speed of the gas, which increases the density.…”
Section: The Disappearances Of Type-b Qpossupporting
confidence: 75%
“…The results show that the Comptonization flux decreases when the disk tears, probably because the outer disc cannot maintain a sufficient gas supply (Liska et al 2021). Conversely, disk flux less than 2 keV increases slightly, which is also seen in recent simulations of Musoke et al (2022), although their main research is not type-B QPOs. They suggested that the absence of a warp in the aligned portion of the disk reduces the inflow speed of the gas, which increases the density.…”
Section: The Disappearances Of Type-b Qpossupporting
confidence: 75%
“…(Liska et al 2021). Conversely, a disk flux less than 2 keV increases slightly, which is also seen in recent simulations of Musoke et al (2022), although their main research is not type-B QPOs. They suggested that the absence of a warp in the aligned portion of the disk reduces the inflow speed of the gas, which increases the density.…”
Section: The Disappearances Of Type-b Qpossupporting
confidence: 72%
“…Liska et al (2019a) demonstrated, for the first time in GRMHD, that tilted thin magnetized disks align with the black hole midplane as theoretically predicted (Bardeen & Petterson 1975), solving a 40 yr old problem in astrophysical disk dynamics. Further, not only this article but also Liska et al (2021) and Musoke et al (2022) simulated disk tearing in highly tilted thin disks (Figure 3), potentially explaining some types of QPOs observed in XRBs (e.g., Kalamkar et al 2016), as well as holding important consequences for galactic evolution (e.g., King et al 2005). Using H-AMR, Chatterjee et al (2019) simulated the longest extent (in both temporal and spatial dimensions) relativistic jets from an accreting black hole in 2D GRMHD, making it possible to follow the jet over a range of 5 orders of magnitude in distance and enable the study of the jet's deceleration process as it carves out its path through the environment.…”
Section: Advancements In Computational Methodsmentioning
confidence: 88%